Sustainability science and technology : an introduction - De Las Heras, Alejandro (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"This book builds a bridge between sustainability science and engineering. It provides the latest information on sustainability issues and solutions by discussing them from basic concepts to scientific consensus to technical solutions. It identifies and addresses the major issues related to sustainability with an environmental science perspective, and presents the connections and interactions between science and technology through a very practical approach and easy understanding. "--
Includes bibliographical references and index.
Keywords: Sustainability; Sustainable development -- Technological innovations; Environmental responsibility; NATURE / Ecology; NATURE / Environmental Conservation & Protection; TECHNOLOGY & ENGINEERING / Environmental / General